2015
DOI: 10.1111/ldrp.12084
|View full text |Cite
|
Sign up to set email alerts
|

The Next Big Idea: A Framework for Integrated Academic and Behavioral Intensive Intervention

Abstract: Despite advances in evidence-based core instruction and intervention, many students with disabilities continue to achieve poor academic and behavioral outcomes. Many of these students are not sufficiently responsive to standardized programs and require more intensive, individualized supports. While many interventions and school problem-solving teams focus primarily on either academic or behavioral concerns, students with the most intensive needs often have interrelated needs in both areas. The next big idea in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…In DBI, ongoing progress-monitoring data are used to gauge students' response to interventions and to determine when adjustments are needed. DBI is not a manualized program; it is a continual process linking data to intervention to improve student outcomes (Berry Kuhle, Zumeta Edmonds, Danielson, Peterson, & Riley-Tillman, 2015).…”
mentioning
confidence: 99%
“…In DBI, ongoing progress-monitoring data are used to gauge students' response to interventions and to determine when adjustments are needed. DBI is not a manualized program; it is a continual process linking data to intervention to improve student outcomes (Berry Kuhle, Zumeta Edmonds, Danielson, Peterson, & Riley-Tillman, 2015).…”
mentioning
confidence: 99%
“…Students who have intense behavioral challenges are particularly at risk for impaired academic engagement and poor achievement outcomes (Kuchle et al, 2015;McIntosh et al, 2008). The range of challenging behaviors manifested in classrooms varies from nondangerous but disruptive to behavior that is potentially harmful to the child exhibiting the behavior or others within the classroom (C. M. Anderson & Rodriguez, 2014;Martin et al, 2012).…”
Section: Context and Needmentioning
confidence: 99%
“…Indeed, research has demonstrated that adapting or modifying interventions along a range of dimensions has led to improvements for students in both academics and behavior within the context of standard, Tier 2 interventions (e.g., Maggin, Zurheide, Pickett, & Baillie, 2015). To systematize this process of intervention intensification, these manipulations are conducted within the context of evidence-based practice, progress monitoring, and diagnostic assessment (Berry Kuchle, Zumeta Edmonds, Danielson, Peterson, & Riley-Tillman, 2015). In the following paragraphs, we provide an overview of three core processes of the DBI framework that are central to the issues addressed in the current special issue.…”
Section: Intensive Interventions: Background and Foundationsmentioning
confidence: 99%
“…The second core feature of the DBI process is the need for interventionists to systematically monitor student progress throughout the intervention and intensification process (Gandhi, Vaughn, Stelitano, Scala, & Danielson, 2015). Broadly speaking, progress monitoring refers to the process of collecting repeated measures of an outcome behavior or target skill over a period of time (Berry Kuchle et al, 2015). There are a number of validated instruments available to school personnel for tracking a range of academic, behavioral, and social outcomes, as well as alternative approaches which can be used in a flexible manner and adapted for a range of targeted outcomes (e.g., Riley-Tillman, Kalberer, & Chafouleas, 2005).…”
Section: Intensive Interventions: Background and Foundationsmentioning
confidence: 99%